Strengthening Writing Skill Using Duolingo and Grammarly Di Panti Asuhan Tat Twan Asi Denpasar - Monny, Maria Osmunda Eawea; Agus Ari Iswara; Evelyn Angelita Pinondang Manurung (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This Community Service Activity aimed to improve English language mastery skills, especially the acquisition of vocabulary and grammar and continued with the Grammarly application to enhance grammar to a more advanced level. This activity was carried out at Tat Twam Asi-Denpasar Orphanage and was attended by 22 participants who were children from the orphanage who were middle and high school students. The Duolingo and Grammarly applications were chosen because these two applications are quite easy to use and can be downloaded and installed on cell phones and personal computers. This activity can be carried out on the spot because of the stable internet network at PKM partners. This activity was carried out for 2 days, where the first day was the Duolingo application activity and the second day was the Grammarly application. The results of this activity show that the participants have enthusiasm for learning vocabulary and grammar which the participants need at school and will then use when the participants have jobs in the future.